KAJIAN KUALITAS AIR PADA BUDIDAYA KERAPU MACAN (Epinephelus fuscoguttatus) SISTEM TUMPANG SARI DI AREAL MANGROVE - Hidayat Suryanto Suwoyo (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
Intercropping pond is a mix between ponds and mangrove forests thathave been developed by farmers because it has a double advantage in additionto participating in the rehabilitation of mangrove forests, can also be used foraquaculture. The research objective was to determine the dynamics of severalwaterqualityparameters onthecultivationof tigergrouper(Epinephelus fuscoguttatus) in ponds intercropping pattern of trenches in the areaof mangrove ponds with different stocking solid. Intercroppingponds usedmeasuring 10 x 120 m2 planted mangrove trees with a spacing of 2-4 perm2and has over 10 years old. Pond is sealed with a waring (0.3 inch diameter) into 9units of research plots measuring 10 x 10 m2. Test animals used were tigergrouper seed weight and the average length of the initial 54.18 g / 13.53 cm tailand stocked with different densities, namely A). 10 tail /100 m2 (1000 fish/ ha); B). 20 tail /100 m2(2,000 fish / ha) and C). 40 tail /100 m2 (4,000 fish/ ha). Water quality parameters are monitored is dissolved oxygen, temperature,salinity, pH, Total Organic Materials (BOT), ammonia, nitrite, and nitrate.Data were analyzed descriptively with the help of graphs.The results showedthat the range of water quality parameters (except salinity) during themaintenance is in the range of a decent life for growth and tiger grouper. Finalweight ranged tiger from 94.50 to 114.2 g / tail and the survival rate of 62-90%.